Exploring The Final-Year Undergraduate Research Related to TikTok, Study Motivation, and Data Mining: A Bibliometric Study - Sulidar Fitri; Panyaporn Prangjarote; Nilubon Kurubanjerdjit (Unversitas Muhammadiyah Mataram, 2026)
TikTok, as a short video-based platform, is now widely used by students to find learning motivation through content such as study tips, time management, and thesis experiences. This study aims to map the scientific literature that examines the relationship between TikTok, learning motivation, and data mining techniques in the context of final year students. The method used is bibliometric analysis with the Scopus database, covering publications between 2019 and 2025. The results showed a significant increase in publication trends in the last three years. India, the United States and China were recorded as the countries with the highest contributions on this topic. Articles with the highest citations tended to address the integration of learning technologies, the use of data mining, and the influence of social media on academic performance. Co-occurrence analysis revealed nine major thematic clusters that show close interrelationships between keywords such as student motivation, academic performance, and educational data mining. This research contributes to understanding the scientific landscape of TikTok utilization in supporting learning motivation and offers further research directions.